Would High Commitment Management work in cultural context of Kazakhstan? - Abenov, Askar (2009)
This thesis argues that “culture matters” (Brook, T., 2002: 28) and inquires whether high commitment management (HCM) often advocated as ‘best practice’, fits Kazakh culture. Therefore, single profile of Kazakhstan on all 5 Hofstede’s (1991) dimensions was drawn first, for which findings of this work and inferences from the available research were utilized. Hereby, Kazakh culture is characterized by low long-term orientation (LTO), high masculinity (MAS), high uncertainty avoidance (UA) and power distance (PD), and low individualism (IND). However, using the same cultural framework of Hofstede it was found that HCM is more likely to be eligible for culture with high LTO, low MAS, UA, PD, and mid-ranged IND (e.g. Norway, Sweden). Thus, the case study shows that Kazakh culture is direct antithesis of what HCM is moulded for. That is, this dissertation concludes that HCM is not designed for Kazakh context, and, therefore, is unlikely to work and be successfully introduced in Kazakh business environment.